Empowering Students in the Digital Era: An Analysis of Interactive E-Modules' Effect on Digital Mathematical Communication - Weylin; Raharjo, Hendri; Haqq, Arif Abdul; Larsari, Vahid Norouzi (EDUPEDIA Publisher, 2023)
Students' mathematical digital communication abilities are paramount in the current digital era, yet many continue encountering difficulties. This study focuses on using interactive e-modules as an innovative learning medium to enhance these abilities. Adopting a quantitative experimental approach, this research involved grade 8students from SMP Negeri 1 Ciwaringin during the 2022/2023 academic year, allocating them into control and experimental groups. The study aimed to evaluate student responses to the e-module, compare students' mathematical digital communication abilities before and after the module's implementation, and determine the effectiveness of the e-module. The study's results showed a significant improvement in students' abilities, with a 75.5% positive response to the e-module and an average student score increase from 36.63 (pretest) to 72.56 (posttest). An N-Gain rise of 56.62% demonstrated the effectiveness of the e-module. These findings solidify the interactive e-module as a suitable learning medium that increases student enthusiasm and participation in mathematical learning. Thus, this research significantly contributes to mathematics education, demonstrating that interactive e-modules can effectively overcome challenges in teaching mathematical digital communication.